UPAYA MENINGKATKAN HASIL BELAJAR SISWA TENTANG PESAN MELALUI TELEPON DENGAN METODE PEMODELAN SISWA KELAS IV SD NEGERI 111 PEKANBARU - Artuti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
Low student learning outcomes are due to a less precise selection of learning methods that suit the subject matter presented to the students. Efforts to overcome this necessitate a method or a proper way so that every student is able to receive information in every lesson well. Stages for easy entry of information include listening, writing or drawing, and then viewing and conducting their own experiments. To address this, the researchers conducted classroom action research by applying methods of modeling. The subjects were fourth-grade students of SD Negeri 111 Pekanbaru with a total of 30 students. This research was conducted over 2 cycles. Data collection techniques used were observation of the activities of teachers and students, and achievement tests.Research suggests that the application of modeling methods can improve learning outcomes in Indonesian language, specifically on the material of conveying a message over the phone. This is evidenced by: (a) an increase in the activity of the teacher. In the first cycle, the first meeting obtained a